Fascists, Fabricators and Fantasists: Anti-Semitism in South Africa from 1948 to the Present - Du Plessis, Willem (Journal of Central and Eastern European African Studies, 2025)
"Fascists, Fabricators and Fantasists: Anti-Semitism in South Africa from 1948 to the Present. In the third volume of Milton Shain's history of antisemitism in South Africa, he traces and unpacks hostile attitudes towards Jews and irrational fantasies that accompany them in apartheid and post-apartheid South Africa."